Novel Technique for Developing E-Textiles: Printing MXene Supercapacitors on Fabrics for Wearable Electronics - Shandra, Anastasiia (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2025)
The increasing demand for miniaturised and flexible wearable electronics is driving the rapid growth of electronic textiles (e-textiles). In this context, microsupercapacitors (MSCs) are becoming essential as energy storage solutions, offering high-power density and extended lifespans. Herein, a novel approach is introduced using aerosol-jet printing (AJP) to fabricate e-textiles with additive-free and pseudocapacitive Ti3C2Tx MXene ink. AJP offers superior resolution and cost-effectiveness for rapid prototyping, while Ti3C2Tx exhibits excellent electrical conductivity, solution-processability, electrochemical activity, and mechanical flexibility. Our printed flexible MXene@Fabric electrodes achieve high areal capacitance of up to 4.387 F cm-2, great rate capability, excellent cyclability, and good washability. The fabricated current collector-free symmetrical MSCs on cotton deliver an areal capacitance of 381 mF cm-2 (at 2 mV s-1) in poly(vinyl alcohol)/sulfuric acid gel electrolyte, outperforming up-to-date printed MXene/textile-based MSCs. These findings demonstrate the transformative potential of integrating MSCs via AJP, paving the way for enhanced energy storage in a wide variety of flexible, breathable, and washable textile-based devices, thereby catalysing a paradigm shift in wearable electronics.
APPROVED
Keywords: e-textiles; MXenes; flexible microsupercapacitors; aerosol jet printing; wearable electronics; energy storage; additive manufacturing